Comparative Study of Thermal Performance of Different Nanofluids in a Double Backward-Facing Step Channel: A Numerical Approach - Shailendra Rana; Hari Bahadur Dura; Sudip Bhattrai; Rajendra Shrestha (International Journal of Chemical Engineering)
Two-dimensional numerical simulations are conducted to study forced convection flow of different water-based nanofluids (ZnO, Al2O3, and SiO2) with volume fractions (ϕ) = 0–5% and fixed nanoparticle size (dp) = 20 nm for Reynolds numbers (Re) = 50–225 over a double backward-facing step with an expansion ratio (ER) = 2 under constant heat flux (q″ = 3000 W/m2) condition using the finite volume method. Results indicate that the local Nusselt number increases with volume fraction and Reynolds number for all working fluids. In comparison to water, the maximum heat transfer augmentation of about 21.22% was achieved by using water-SiO2 nanofluid at Re = 225 with ϕ = 5% and dp = 20 nm. Under similar conditions, the Al2O3 and ZnO nanofluids demonstrated 14.23% and 11.86% augmentation in heat transfer in comparison to water. The skin friction coefficient decreases with the increase in Re for all working fluids. No significant differences are observed in the values of skin friction coefficient among all working fluids at a particular Re. These results indicate that the heat transfer enhancement has been achieved with no increased energy requirements. In addition, the velocity increases with the rise in Re, with SiO2 nanofluid exhibiting the highest velocity as compared to other working fluids.